A competitive amino-carboxylic hydrogen bond on a gold surface. Issue 26 (27th February 2015) - Feng, Zhijing; Castellarin Cudia, Carla; Floreano, Luca; Morgante, Alberto; Comelli, Giovanni; Dri, Carlo; Cossaro, Albano
Abstract : A novel amino-carboxylic hetero-synthon is described, which drives the formation of a complex 2D hetero-organic architecture. Abstract : An amino-carboxylic motif is identified as a novel synthon in the formation of 2D hetero-organic architectures at surfaces. The well-defined interacting scheme we describe herein represents an ideal prototypical system for further investigation of the interaction at surfaces of the two functional groups.